IMPLEMENTASI PERIZINAN PEREDARAN OBAT NARKOTIKA DI KOTA DENPASAR - Adiwijaya, Nyoman Setiawan; Wairocana, I Gusti Ngurah; Dahana, Cokorda Dalem (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
Implementation of regional autonomy should be oriented towardsimproving the welfare of society. To realize the ideals of the Indonesianation will require sustained effort in all areas where one of the efforts isby give attention to health care and pharmacy services by setting theavailability and abuse prevention dangerous drugs, narcotics traffickingand abuse. To achieve those objectives and monitoring efforts are needed tocontrol the distribution of narcotics official order type and amount of needsaccording to the the real needs of the public, through the issuance of apharmacy license as the official distribution of narcotics.
Keywords: admission, regional autonomy, authorithy, narcotics